ANALISIS BUKU TEKS SEJARAH KELAS XI DALAM PEMBELAJARAN DARING DI SMA NEGERI 1 KEBOMAS - Shovi Wiranata Febriani (Universitas Negeri Malang, 2021)
The use of history textbooks can be useful for teachers as a supporting medium in delivering learning materials that are adjusted to the applicable curriculum. History textbooks contain learning materials and a variety of practice questions. History textbook analysis is done in order to formation of conformity and suitability from the books to be distributed. The feasibility of a textbook is be observed the feasibility from the content and the worthiness of presentation. That way, the textbook will have the right quality or purpose for students so as students competent to graps learning material well. Each school uses a different learning method in the middle of an online learning system. At SMA Negeri 1 Kebomas uses a curriculum for independent learning or independent learning in accordance with the assessment instrument for high school history textbooks. The use of an independent learning curriculum makes student achievement, skill ability, and level of understanding increase. This research aims to intends the analysis of history textbooks for class XI in online learning at SMA Negeri 1 Kebomas using qualitative methods and literature study.Penggunaan buku teks sejarah mampu bermanfaat bagi guru sebagai media penunjang dalam penyampaian bahan pelajaran yang sesuaikan pada kurikulum yang berlaku. Buku teks sejarah berisi mengenai bahan pelajaran dan beragamnya latihan soal. Analisis buku teks sejarah dilakukan guna terbentuknya kesesuaian dan kelayakan buku yang akan didistribusikan. Kelayakan suatu buku teks dilihat dari kelayakan isi dan kelayakan penyajian. Dengan begitu, buku teks akan memiliki mutu serta tujuan yang tepat bagi siswa sehingga siswa mampu memahami materi dengan baik. Setiap sekolah menggunakan metode pembelajaran berbeda di tengah sistem pembelajaran daring yang dilakukan. Di SMA Negeri 1 Kebomas menggunakan kurikulum merdeka belajar atau kemandirian belajar yang sesuai dengan intrumen penilaian buku teks sejarah SMA. Penggunaan kurikulum merdeka belajar membuat prestasi, kemampuan keterampilan, dan tingkat pemahaman siswa dapat meningkat. Penelitian ini bertujuan untuk mengetahui analisis buku teks sejarah kelas XI dalam pembelajaran daring di SMA Negeri 1 Kebomas dengan menggunakan metode kualitatif dan studi pustaka.